Performance on the traditional and the touch screen, tablet versions of the Corsi Block and the Tower of Hanoi tasks. - Robinson, Sarita J.; Brewer, Gayle (Computers in Human Behavior, 2016)
Psychologists routinely administer cognitive tasks to assess a range of mental abilities. In recent years, researchers and practitioners have employed new (i.e. digital) technologies to test cognitive performance, with tablet computer based tasks often replacing traditional versions. However, the extent to which findings from traditional and touch screen tablet based tasks are equivalent remains unclear. In the present study, sixty participants (18 men and 42 women) completed both the Tower of Hanoi and Corsi Block tasks in their traditional (wooden) form and using a touch screen tablet. Performance outcome measures (span length, number of moves, and time taken) were recorded alongside subjective workload for each task. Findings revealed that number of moves and span length do not significantly differ between the traditional and tablet based versions of each task. However, the computerized Tower of Hanoi task was completed more quickly than the traditional version. Differences were noted for subjective workload with higher physical demand reported for the traditional versions of each task. Participants also reported the traditional Tower of Hanoi task to be more enjoyable but more mentally demanding. In conclusion, the touch screen versions of the Tower of Hanoi and Corsi Block tasks appear largely equivalent to the traditional versions.